The Dynamics of Seniority Culture in Shaping Female Students' Discipline at Darul Iman Modern Islamic Boarding School, Kutacane, Southeast Aceh - Mina Fitri; Mira Fauziah; Rofiqa Duri (Jurnal Kajian dan Pengembangan Umat, 2026)
The culture of seniority is a guidance system implemented in “pesantren” (Islamic boarding schools) to foster discipline among female students through mentoring, role modeling, and supervision. Nevertheless, various rule violations still occur among the students, such as skipping congregational prayers, causing disturbances during lessons, violating language usage regulations, and failing to maintain environmental cleanliness. This study aims to describe the discipline of female students and analyze the factors hindering its development through the seniority culture at the Darul Iman Modern Islamic Boarding School in Kutacane, Southeast Aceh. The study employs a descriptive qualitative approach involving five informants: two junior students, two senior students, and one female supervisor “ustazah”. Data were collected through observation, in-depth interviews, and documentation, and subsequently analyzed using the Miles and Huberman model. The results indicate that the seniority culture plays a role in shaping discipline regarding security, religious observance, academics, language, and cleanliness through habituation, mentoring, and role modeling. Identified obstacles include low self-awareness, peer group influence, inconsistent adherence to the seniority culture, boredom with boarding school routines, and limited supervision. The study concludes that the seniority culture is effective in internalizing disciplined character when implemented consistently with the support of all elements within the boarding school.